THE ROLE OF PPKn TEACHERS IN INSTILLING RELIGIOUS CHARACTER VALUES IN STUDENTS OF SMA NEGERI 5 TERNATE CITY - Jainudin Abdullah; Rustam Hasim (SOSIOEDUKASI, 2025)
Instilling religious character values is an important part in shaping the personality of students with noble and responsible character. Pancasila and Citizenship Education Teachers (PPKn) have a strategic role in instilling these values through the learning process and example. This study aims to describe the role of PPKn teachers in instilling religious character values in students at SMA Negeri 5 Ternate City and identify its supporting and inhibiting factors. This study uses a descriptive qualitative approach with data collection techniques in the form of observation, interviews, and documentation. The results of the study show that PPKn teachers at SMA Negeri 5 Ternate City play a role as facilitators, motivators, and role models in fostering students' religious character, such as faith values, tolerance between religious communities, honesty, and discipline. These values are instilled through integration in subject matter, religious habituation activities in schools, and through a personal approach to students. However, there are several obstacles faced, such as the lack of parental participation, the influence of the environment outside the school, and limited time in the learning process. This study recommends the need for collaboration between schools, teachers, and parents in supporting the strengthening of students' religious character in an ongoing manner.